Gestión digital de expedientes en Sysco - Salas-Vargas, Luis Emilio (Instituto Tecnológico de Costa Rica, 2023)
This project aims to improve the management and security of personnel records in the company Sysco Systems Consultants through the development of a technological solution using React. Managing physical records in the human resources area presents difficulties such as lack of accessibility, the risk of loss or damage to records, inefficiency in information management, and vulnerability to security issues. To address these problems, it is proposed to develop a front-end solution using React, establish a bidirectional connection with the back-end to access and communicate with the database, ensure scalability and flexibility of the solution, and perform user and functionality testing. The HR management application will digitize the records, allowing easy access to information, streamlining decision-making, reducing the risks of data loss or damage, and improving efficiency in management. The project is justified by the importance of adequately protecting and maintaining records, accessing information remotely, making strategic and operational decisions, and contributing to digital transformation. The literature review highlights the importance of document management in human resources and the impact of technology on this process. The use of React to build the web application provides an attractive user experience, efficient performance, and ease of integration with other technologies. The implementation of this system improves decision-making and promotes digital transformation within the company.
Práctica profesional (Bachillerato en Ingeniería en Computación) Instituto Tecnológico de Costa Rica, Carrera de Ingeniería en Computación, 2023.
Keywords: Materiales de archivo - Digitalización; Desarrollo de sitios web - React; Interfaces de usuario - Eficacia; Desarrollo de software